2017
DOI: 10.1177/0049085717730248
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Senapur: Reflections on Agrarian Changes in North India

Abstract: Through a revisit study in 2013, this article attempts to explore agrarian relations in Senapur, a village located in eastern Uttar Pradesh. Research reveals that landlessness remains concentrated amongst dalits as does the continuing hold of ‘upper castes’ on land. When inheritance acts as the primary mode of transfer of landed property in the absence of market-mediated and state-mediated transactions, two results are evident: a decrease in the size of holdings due to the subdivision of property and simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In Uttar Pradesh (UP), the largest state of India, where historically the proportion of agricultural labour has been relatively low, the proportion of cultivators to main workers in rural areas saw a sudden drop of twelve percentage points, while the proportion of agricultural labour went up by seven percentage points between 2001 and 2011. Studies have shown that the mechanisation of several agricultural operations along with changing crop patterns has offset not only the potential employment opportunities generated by the increase in crop intensity but also reduced the annual earnings of workers despite wages going up during peak season (Trivedi, 2017).…”
Section: The Dalit Capitalism Manifestomentioning
confidence: 99%
“…In Uttar Pradesh (UP), the largest state of India, where historically the proportion of agricultural labour has been relatively low, the proportion of cultivators to main workers in rural areas saw a sudden drop of twelve percentage points, while the proportion of agricultural labour went up by seven percentage points between 2001 and 2011. Studies have shown that the mechanisation of several agricultural operations along with changing crop patterns has offset not only the potential employment opportunities generated by the increase in crop intensity but also reduced the annual earnings of workers despite wages going up during peak season (Trivedi, 2017).…”
Section: The Dalit Capitalism Manifestomentioning
confidence: 99%
“…However, new evidence suggested that farm households earned a substantial share of their income from non-agricultural sources, but agriculture income continued to act as a foundation on which diversification edifice was constructed. It meant that households with larger agricultural income also earned larger non-agriculture income (Trivedi 2017).…”
Section: The Question Of Viability Of Small Farmsmentioning
confidence: 99%